Air temperature and atmospheric pressure measured every 10 minutes at a summer dike, Butjadingen, Germany (Nov 2022–Nov 2023) - Schönebeck, Jan-Michael; Bunzel, Dorothea; Paul, Maike; Schlurmann, Torsten (In: Schönebeck, J-M et al. (2025): Soil temperature, volumetric water content, electrical conductivity, air temperature and atmospheric pressure measured every 10 minutes in a grass- and a herb-dominated area at a summer dike, Butjadingen, Germany (Nov 2022–Nov 2023) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.987380, 2025)
The logger was mounted on the southern (inland) side of a summer dike, which is located at the south-eastern North Sea coast of Germany (Butjadingen, Wesermarsch; 'Mix-Grass': 53.61211876 ° N, 8.330925695° E, 'Mix-Herb': 53. 61210826° N, 8.330989015° E), about 1 m below the dike crest. The dike height is approximately 3.6 m above mean high water (MHW). The measurement data was logged at 10-minute intervals using a ZL6 logger from the METER Group.
Keywords: coast; dikes; North Sea